The Relationship Of The Neoliberal Paradigm To Value Orientation And Managerial Practices In Islamic Educational Institutions - Ahmad Andy Setiady; Irawan Irawan; Rohmat Mulyana Sapdi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines the dynamics of correlation of the neoliberal paradigm in the management of Islamic educational institutions, particularly the relationship between the neoliberal paradigm, value orientation, and management practices. In contemporary educational management discourse, neoliberalism emphasizes the principles of efficiency, accountability, competition, and performance orientation, which have the potential to influence the governance of educational institutions, including Islamic boarding schools. This study aims to analyze the relationship between the neoliberal paradigm and value orientation and managerial practices at the Darul Falah Islamic Boarding School in West Bandung. The study used a quantitative approach with a survey method using a questionnaire compiled based on research variable indicators. The research sample consisted of 35 respondents selected using probability sampling techniques. Data analysis was performed using SPSS through the Shapiro–Wilk normality test and the Spearman Rank nonparametric correlation test. The results showed that the neoliberal paradigm has a positive and significant relationship with value orientation (r = 0.401; Sig = 0.017), but has a weak and insignificant positive relationship with management practices (r = 0.308; Sig = 0.072). In addition, value orientation has a strong and significant relationship with management practices (r = 0.682; Sig = 0.000). These findings indicate that the influence of neoliberalism is selective, where Islamic educational values ​​remain a dominant factor in the management practices of Islamic educational institutions